152 Competency-based training in translational research: A curriculum crosswalk for enhanced mentorship in NIH Career Development Programs - Holly Zink; Holly R. Zink; Jennifer Goldman; Matthew W. Mosconi; Jacob Sosnoff; Nikki Nollen (Journal of Clinical and Translational Science)
Objectives/Goals: This poster details the development, implementation, and assessment of a comprehensive competency-based curriculum crosswalk and training plan aimed at enhancing the mentorship and skill development of translational research mentees within the National Institutes of Health (NIH) KL2 and TL1 Career Development Award programs. Methods/Study Population: The Center for the Improvement of Mentored Experiences in Research (CIMER) Mentoring Up for Early Career Investigators program, first developed by the University of Wisconsin-Madison, was further adapted by the Frontiers Clinical and Translational Science Institute (Frontiers CTSI). A competency crosswalk illustrates connections between a training curriculum and expected competencies. Developing a competency-based training crosswalk is a strategic approach designed to align mentoring practices with established NIH competencies, including the Seven Characteristics of a Translational Scientist, Mentoring Competency Assessment, Responsible Conduct of Research, Translational Teams, and TeamMAPPS. Results/Anticipated Results: The KL2 and TL1 Award Programs serve as ideal platforms for applying the developed curriculum. Implementing a competency-based, evidence-based, and culturally responsive curriculum for research mentee training has shown substantial benefits. Our pilot tests and full-scale implementation within the KL2 and TL1 Award Programs have demonstrated marked improvements in mentee competencies, such as technical skills, research design, and professional development as shown through evaluation feedback. Integrating the new Frontiers CTSI curriculum has fostered more effective and supportive mentoring relationships. Mentees have reported high satisfaction levels with the training program, particularly appreciating the interactive didactics, continuous feedback mechanisms, and reflective practices. Discussion/Significance of Impact: By adopting these recommendations, Clinical and Translational Science Awards (CTSA) and similar programs can improve research mentorship quality and impact, fostering a diverse cohort of skilled researchers. Implementing these strategies in CTSA mentorship programs offers a model for broader application in research training.